Analysis of the phenomenon of the alternation and rotation between Arabic letters in Twitter - Ismail, Alanazi Nujud; Abdul Jabar, Mohd Azidan; Mohamad, Ab Halim; Hassan, Abd Rauf (Science and Engineering Research Support Society, 2020)
Classical Arabic is affected by some unfamiliar phenomena, such as the phenomenon of alternation between letters and others. Therefore, this study aims to monitor the places of alternation and substitution in the usage of (prepositions and conjunctions) by “twitter” users, to identify the effects of this phenomenon on proper way of writing Arabic language and its eloquence on social networking sites generally and twitter in particular, and to know whether it constitutes a communication or understanding gap between the readers and writers, with the objective of creating a third-party application for evaluating the usage of compositions and conjunctions on “twitter” in the near future. The study adopts the descriptive and analytical methodology to collect and analyse the data of not less than 200 political and social Arabic tweets that contain the usage of prepositions and conjunctions between 2017 and 2018, for the study. It also uses SPSS data analysis to run a set of statistical tests, in order to know the frequency of using alternations between the letters on social networking sites. The study concludes that the phenomenon of alternation and rotation between letters is very common among the Arab writers on twitter. The highest percentage of the error in the prepositions appeared to be 82%, and the lowest percentage of 18% goes to the conjunctions.It also finds that this phenomenon does not constitute a communication gap between the readers and writers, and not affect their understanding; due to the positive feedback, responses, and repost by the readers; which is considered a real threat to classical Arabic language, because it will lead to its declination. Hence, the research recommends hard working on the steadfastness and survival of the Arabic language by its speakers.